KUALITAS PRODUK SEBAGAI PREDIKTOR KEPUASAN KONSUMEN REMAJA PEREMPUAN GENERASI Z DALAM PENGGUNAAN SKINCARE - Heru Valentino Saekoko.; Sutarto Wijono (Bajang Institute, 2025)
This study is motivated by the importance of product quality as a key factor influencing consumer satisfaction, particularly in the rapidly growing skincare industry among Generation Z female adolescents. The purpose of this research is to examine the role of product quality as a predictor of consumer satisfaction. A quantitative approach was employed using a survey method, with a questionnaire distributed online to 271 Generation Z female adolescents who use Wardah skincare products. The sampling technique applied was purposive sampling. Data were analyzed using simple linear regression. The findings reveal that product quality has a significant effect on consumer satisfaction, with a significance value of 0.000 (p < 0.05) and R² of 0.053 (p < 0.05). Most respondents rated product quality and consumer satisfaction at a moderate level. These results confirm that the higher the perceived product quality, the greater the level of consumer satisfaction achieved. The implication of this study is that companies need to continuously improve product quality in terms of effectiveness, ingredient safety, and formula innovation that aligns with Generation Z’s preferences. Furthermore, this research provides a foundation for future studies to explore other variables that may also influence consumer satisfaction